Fatty acid analysis reveals the trophic interactions among organisms in the Zhelin Bay Marine Ranch - Li, Changlin; Lin, Huijie; Guo, Yu; Yu, Gang; Ma, Zhenhua; Pei, Kun; Qin, Chuanxin (Frontiers in Marine Science, 2023)
The fatty acid composition in organisms can reflect the trophic level, feeding habits, and utilization of local resources. In the present study, the living resources of different functional areas (artificial reef area, shellfish area, macroalgae area) in the Zhelin Bay Marine Ranch were investigated, and fatty acid analysis was used to elucidate the trophic relations across the food web. The results showed that 22:6ω3 FA (docosahexaenoic acid, DHA), 20:5ω3 FA (eicosapentaenoic acid, EPA), 16:1ω7 FA, and 16:0 FA are fatty acid biomarkers that distinguish carnivorous, omnivorous, and herbivorous organisms. The ratios of DHA/EPA, polyunsaturated fatty acids/saturated fatty acids (PUFA/SFA), and sum of ω3 fatty acids/sum of ω6 fatty acids (Σω3/Σω6) can be used as an important basis to assess the trophic level and feeding habits of organisms. In the comparison of the food web structure of different functional areas, the DHA/EPA ratio of carnivorous organisms in the Artificial Reef area was higher than that in other functional areas due to the abundant living resources, indicating that the food web of the Artificial Reef area presents lower stability to cope with perturbations. Furthermore, MixSIAR was used to quantitatively estimate the diet composition of consumers in the Zhelin Bay Marine Ranch based on their fatty acids. The results of the present study are a valuable contribution to understanding the trophic relationships in the Zhelin Bay Marine Ranch and provide theoretical support for future planning and construction of marine ranches.